INFLUENCE OF FEEDING CORN IMPURITIES ON RUMEN BACTERIA AND FERMENTATION CHARACTERISTICS OF SHEEP - Thaer A. M. Al-Mamouri; J. A. Tawfeeq Al-Ani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to determine the effect of replacing treated and untreated corn impurities with urea instead of wheat bran on rumen bacteria and fermentation of Awassi lambs. Five levels of treated and untreated corn impurities as 44:0%, 32:11%, 20:22%, 10:32% and 0:39% bran:impurities in a 2×5 factorial experiment/ Completely Randomized Design using forty lambs with an initial weight of 27.45 ± 2.16kg and 4-5 months old. Individual feeding was used for 70 days and rumen fluid was sampled at 0, 3, 6h after morning feeding. Results showed an increasing (p